1974
DOI: 10.1159/000180386
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of <i>p</i>-Aminohippurate and its Relevance in Man

Abstract: p-Aminohippurate (PAH) clearance studies were carried out on 15 patients suffering from renal disorders of different origin. In 6 patients the two kidneys were tested separately. It could be shown that in the human organism PAH undergoes partial metabolization resulting in the production of p-aminobenzoate (PAB), N-acetyl-PAH and N-acetyl-PAB. Distribution pattern of PAH and its metabolites is different in urine and blood samples: there is more N-acetyl-PAH in the urine than in the blood. Benzoates make up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…As shown in figure I, the venous out flow contained only PAB and A-acetylated metabolites, but not PAH. This is in accord ance with results obtained in situ [14,18], Con sequently, the term 'PAH extraction ratio' is of no value in the isolated rat kidney either: 'Ei*ah', determined with the commonly used assay does not represent the fractional ex traction of PAH. It reflects a more or less complete extraction ratio of several aromatic amines.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As shown in figure I, the venous out flow contained only PAB and A-acetylated metabolites, but not PAH. This is in accord ance with results obtained in situ [14,18], Con sequently, the term 'PAH extraction ratio' is of no value in the isolated rat kidney either: 'Ei*ah', determined with the commonly used assay does not represent the fractional ex traction of PAH. It reflects a more or less complete extraction ratio of several aromatic amines.…”
Section: Discussionsupporting
confidence: 82%
“…The difference between the calculated and the directly measured perfusion flow disappeared only when the PAH assay included all PAH metabolites. This implies that the validity of the C pah determination is influenced by an inconstant conversion rale of PAH as demon strated for the rat kidney in situ [18] and the human kidney [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that renal hypoxia per se is an unlikely cause for the reduced N-acetylation rate of PAH. Chronic hypoxia, however, may alter renal meta bolism by increasing the renal NEFA content which, in turn, inhibits the N-acetyltransferase activity.Recently, evidence has been presented that the renal metabolism of the clearance substance /i-aminohippurate (PAH) (cleavage of the glycin-group, N-acetylation) interferes with the reliability of the determination of the plasma flow [6][7][8]13], This is predominantly due to the different distribution of PAH and of its metabolites in urine and in plasma [13] and to the circumstance that Nacetylated metabolites (N-acetyl-PAH, N-acetyl-p-aminobenzoate) remain undetected by usual chemical analysis [6,13], Furthermore, the rate of N-acetylation of PAH varies largely, as was shown in rats with experimental hypertension and in humans suffering from severe essential hypertension or from renal artery stenosis [6.8.13]. ft was found significantly reduced in the clamped kidney of rats with two-kidney Goldblatt-hypertension (one renal artery clamped, both kidneys in situ), whereas the N-acetylation rate was normal in the contralateral organ [13].…”
mentioning
confidence: 99%
“…I-hippuran has become a useful tool in kinetic investigations due to the ease of its analysis (Magnusson, 1962;Pritchard, et al, 1965;Blaufox, et al, 1963). human, rabbit, pig, guinea pig, mouse, cat, cattle, sheep, and rat (Malyusz, et al, 1979;Carpenter & Mudge, 1980;Smith, et al, 1945;Despopoulos, 1956;Frindt & Vial, 1968;Setchell & Blanch, 1961;Gyrd-Hansen & Rasmussen, 1970;Cross & Taggart, 1950;Girndt, et al, 1974a and1974b), but not in dogs (Mudge & Taggart, 1950b;Newman, et al, 1949). Of these reports, only Setchell and Blanch 1961 catheter at 1, 2, 4, 6, 15, 20, 25, 30, 40, 50, 60, 75, 90, 105, and 120…”
mentioning
confidence: 99%